2020
DOI: 10.1371/journal.pone.0232491
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents’ wealth and the body mass index trajectories of grandchildren

Abstract: Background The aims of this study are to (i) examine associations between grandparents' wealth and grandchild's initial body mass index (BMI) in early childhood and its subsequent growth patterns, and to (ii) assess whether the associations are similar for white and black children. Methods Data are from the U.S. Panel Study of Income Dynamics (PSID) and its supplemental studies of Child Development Supplement (CDS) and Transition to Adulthood (TA) (N = 2,128). Three-level growth curve models are used to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(73 reference statements)
0
3
0
1
Order By: Relevance
“…Most of the babysitters are housewives, and even though they live very simply with few basic needs, this grandmother tries to provide nutritious food to her grandchildren. Grandmother's wealth and economy reflect the economic resources available to the family (Huang, 2020). After attending health education to prevent stunting, it was discovered that the caregiver was trying to save money and grow vegetables and fruits for her grandchildren.…”
Section: Parenting Culture Of Grandmother's Rolementioning
confidence: 99%
“…Most of the babysitters are housewives, and even though they live very simply with few basic needs, this grandmother tries to provide nutritious food to her grandchildren. Grandmother's wealth and economy reflect the economic resources available to the family (Huang, 2020). After attending health education to prevent stunting, it was discovered that the caregiver was trying to save money and grow vegetables and fruits for her grandchildren.…”
Section: Parenting Culture Of Grandmother's Rolementioning
confidence: 99%
“…In Australia, research indicates that family circumstances are transmitted across generations. For instance, Australian children of parents who receive welfare payments are almost twice as likely to be on welfare payments as adults when compared to those who are not (Cobb-Clark et al, 2017), while other work has demonstrated the transmission of outcomes related to wealth (Lersch & Baxter, 2021), health (Huang, 2020) and education (Hancock et al, 2018). One likely mechanism for this intergenerational transmission of individual social and economic outcomes is the influence of parents and parenting.…”
Section: Intergenerational Transmission Of Parenting Practicesmentioning
confidence: 99%
“…Other research has focused on the transmission of educational (dis)advantage from grandparents and parents to children (Hancock et al, 2018), the transmission of health outcomes across generations (Huang, 2020;James et al, 2020), the transmission of attitudes , joblessness (Curry et al, 2019), and the transmission of wealth (Lersch & Baxter, 2020). In sum, there is clear evidence of intergenerational associations which show that the playing field is not level for all children and that if we are to fully understand and address social and economic disadvantage in Australia, we need to understand not only the life course journeys of individuals, but also their family background.…”
Section: Life Course Approaches and Intergenerational Inequality In A...mentioning
confidence: 99%